Sex‐specific newborn screening for X‐linked adrenoleukodystrophy. Issue 1 (26th October 2022) - Albersen, Monique; van der Beek, Samantha L.; Dijkstra, Inge M. E.; Alders, Mariëlle; Barendsen, Rinse W.; Bliek, Jet; Boelen, Anita; Ebberink, Merel S.; Ferdinandusse, Sacha; Goorden, Susan M. I.; Heijboer, Annemieke C.; Jansen, Mandy; et al.
Abstract: Males with X‐linked adrenoleukodystrophy (ALD) are at high risk for developing adrenal insufficiency and/or progressive leukodystrophy (cerebral ALD) at an early age. Pathogenic variants in ABCD1 result in elevated levels of very long‐chain fatty acids (VLCFA), including C26:0‐lysophosphatidylcholine (C26:0‐LPC). Newborn screening for ALD enables prospective monitoring and timely therapeutic intervention, thereby preventing irreversible damage and saving lives. The Dutch Health Council recommended to screen only male newborns for ALD without identifying untreatable conditions associated with elevated C26:0‐LPC, like Zellweger spectrum disorders and single peroxisomal enzyme defects. Here, we present the results of the SCAN (Screening for ALD in the Netherlands) study which is the first sex‐specific newborn screening program worldwide. Males with ALD are identified based on elevated C26:0‐LPC levels, the presence of one X‐chromosome and a variant in ABCD1, in heel prick dried bloodspots. Screening of 71 208 newborns resulted in the identification of four boys with ALD who, following referral to the pediatric neurologist and confirmation of the diagnosis, enrolled in a long‐term follow‐up program. The results of this pilot show the feasibility of employing a boys‐only screening algorithm that identifies males with ALD without identifying untreatable conditions. This approach will be of interest to countries that are considering ALD newborn screening but are reluctant to identify girls with ALD because for girls there is no direct health benefit. We also analyzed whether gestational age, sex, birth weight and age at heel prick blood sampling affect C26:0‐LPC concentrations and demonstrate that these covariates have a minimal effect. Abstract :